2011
DOI: 10.1007/s11145-011-9328-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a brief but intensive remedial computer intervention in a sub-sample of kindergartners with early literacy delays

Abstract: Living Letters is an adaptive game designed to promote children’s combining of how the proper name sounds with their knowledge of how the name looks. A randomized controlled trial (RCT) was used to experimentally test whether priming for attending to the sound-symbol relationship in the proper name can reduce the risk for developing reading problems in the first two grades of primary education. A Web-based computer program with more intensive practice than could be offered by teachers affords activities that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Moreover, positive relations were found between the time that children spent on the computer games and their progress in phonological and letter skills. Another example is a study by Van Der Kooy-Hofland, Bus, and Roskos (2012), who also tested a kindergarten computer program aimed at phonological skills. They showed that children low in preliteracy skills progressed stronger in phonological skills, but not in letter knowledge, compared to a control group.…”
Section: Stimulating Preliteracy Skills With the Computermentioning
confidence: 99%
“…Moreover, positive relations were found between the time that children spent on the computer games and their progress in phonological and letter skills. Another example is a study by Van Der Kooy-Hofland, Bus, and Roskos (2012), who also tested a kindergarten computer program aimed at phonological skills. They showed that children low in preliteracy skills progressed stronger in phonological skills, but not in letter knowledge, compared to a control group.…”
Section: Stimulating Preliteracy Skills With the Computermentioning
confidence: 99%
“…Living Letters promotes understanding of the alphabetic principle, the notion that letters in print relate to sounds in spoken words. The program offers a framework that anchors instruction and practice in a personally motivating context of activities using children's own proper name (van der Kooy-Hofland, Bus, & Roskos, 2012). This approach is based on a series of studies showing that most children can name the initial letter of the own proper name earlier than other letters (Levin, Both-de Vries, Aram, & Bus, 2005) and that the sound of this letter is the first one that children can identify in spoken words and use correctly in spelling (Both-de Vries & Bus, 2008Bus, , 2010.…”
Section: Intervention Programsmentioning
confidence: 99%
“…Ten of the 16 studies deployed individuals who were specially recruited and trained (three of which were 1:1 computer‐based interventions overseen by a trainer/s). Recruited individuals varied considerably and included masters students (Van der Kooy‐Hofland, Bus, & Roskos, ), older adult volunteers (Fives et al, ; Fives, ) and higher‐grade peers, student teachers and volunteers (Regtvoort, Zijlstra, & Leij, ). Four of the 16 interventions were delivered by school staff or TAs.…”
Section: Resultsmentioning
confidence: 99%